Compliance with prescribed medicines: a study of elderly patients in the community - Wandless, Irene (1979)
Compliance with regular medicine taking has been assessed in 81 patients, aged 65 and over, living at home. Interview assessment, home tablet count, and retrospective review of general practice prescription record cards provided three indices of compliance. Deviation by more than 10 per cent from absolute adherence to the prescription was found in 53 per cent of all tablet counts and was significantly more common in women than in men. Errors were also more common when medicines were to be taken more than once daily. The compliance index obtained by inspection of prescription records correlated closely with the index calculated from tablet counts (r(s) = 0·68; p < 0·001) for 129 separate medicines taken regularly. Poor compliance with an individual medicine could be predicted accurately in 66 per cent of cases. A combination of prescription record inspection and interview assessment increased the accuracy of this prediction to 86 per cent. These findings suggest that, using simple methods, the level of compliance can be accurately predicted in a substantial number of elderly patients at home.